International Crude Oil Price Fall: Implication of Adopted CBN’s Restrictive Monetary Policies on SMEs Performance in Nigeria. (International Journal of Scientific Research and Management (IJSRM), 2016)
This study empirically investigated the implication of the adopted restrictive monetary policies on the SMEs. The CBN adopted the restrictive monetary policy as a palliative measure to cushion the unfavourable effect of the plummet of international crude oil price on the macro-economy without a thorough rethink of the effect on micro –economy specifically SMEs in Nigeria. The study is borne out of the curiosity to determine the aftermath of this panic measure adopted by CBN on Small and Medium Scale Enterprises which is the bedrock of any developing economy seeking industrialization like Nigeria. The research work employed Survey research design. The study revealed interestingly that high interest rate discourages investment. But, it further shows that irrespective of the level of interest rate, there are other factors that drive investors to invest more even when the level of interest rate is unfavourable which the study hypothesized as Market or Demand-Side Investment Driven. It is also revealed that CRR actually quarantined money supply which limits the access of the SMEs to credit because not less than 67% of this sector relies on commercial banks credit; Naira devaluation is really a cog in the wheel of SMEs investment and serves as drag to the SMEs performances. The research offered a set of policy prescriptions that is holistic and integrated approach which would make SMEs in Nigeria to be able compete with the foreign competitors, and the industrialization need of the economy can be achieved harmoniously with the nation’s economic growth and socio-economic development